(untitled) (Research, Society and Development, 2023)
The purpose of this cross-sectional study was to evaluate the use of a green propolis-based ointment for the treatment of skin tears in an elderly hospitalized population. Eleven subjects over 60 years old were selected. They were admitted to a general hospital and received local treatment for skin tears during the hospital stay with a green propolis-containing ointment. Personal data was obtained from the hospital admission to identify the patient’s characteristics. Body mass index, alleged allergy to propolis, use of medications, comorbid conditions, degree of dependence (Fugulin scale), and degree of frailty (Rockwood scale) were also obtained. The skin tears were classified using the STAR system. The use of a propolis-containing ointment in skin tears resulted in the improvement of hematomas in the flaps and periflaps of skin tears. In addition, it helped to prevent the colonization and proliferation of bacteria at the injury site, recovering the injured tissue and resulting in viable and quality tissue. No complaints of pain or side-effect events such as signs of tenderness or local or systemic toxicity in the treated patients were reported. The skin tear flaps, darkened by bruises that occurred during the trauma, were gradually absorbed, and the skin improved its surface appearance. The treated tissue presented new and better quality epithelium regardless of treatment time. The ointment containing propolis was effective for the treatment of skin tears. The set of results obtained supported the assumption that propolis-based ointment can be included as an effective option to treat skin tears.